THE LEGALITY OF TRANSACTIONS USING CRYPTOCURRENCY IN THE PERSPECTIVE OF THE MUI FATWA: A FIQH-BASED APPROACH - Ash Shabah, Musyaffa Amin; Kumalasari, Eva Dwi; Aiz, Muhammad (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
Cryptocurrency, including popular digital currencies such as Bitcoin and Ethereum, has rapidly gained prominence as a medium of exchange, sparking significant debate over its compatibility with Islamic finance principles. This study analyses the Indonesian Ulama Council (MUI) fatwa on the permissibility of cryptocurrency transactions using a fiqh-based approach. The study employs a qualitative method with a descriptive-analytical approach, utilising literature review and documentation of the MUI’s Seventh Ijtima’ on Contemporary Fiqh Issues. The analysis focuses on two fiqh principles: la darar wa la dirar and al-dharar yuzal. The study finds that the MUI fatwa declares cryptocurrency transactions impermissible under Islamic law due to the risks of dharar (harm), primarily stemming from high volatility, which introduces gharar (uncertainty) in financial dealings. The extreme fluctuations in cryptocurrency values, the anonymity in transactions, and the absence of comprehensive regulation contribute to financial instability and potential harm to individuals, which contradicts the principles of fairness and risk management in Islamic finance. The fatwa aims to protect Muslims from these risks, affirming that Islamic transactions must avoid uncertainty and harm to any party involved. This research provides valuable insights into ongoing discussions about cryptocurrencies within Islamic financial frameworks. It offers recommendations for policymakers and the public on the appropriate use of cryptocurrencies in a manner aligned with Sharia principles.